”I know that they would play with them cars”: Studying noun phrase complexity in L1 Finnish learners’ of English in upper secondary school - Kairavuo, Katariina (My University, 2023)
The present study focuses on the noun phrase complexity of L1 Finnish learners of English in upper secondary school utilising a high-achieving group of students of a similar age studying in the International Baccalaureate programme that operates in English. The data for the present study is part of a larger corpus collected by the English Department of the University of Turku, that includes both spoken and written samples of Finnish learners of English from comprehensive school to university level as well as data from Swedish-speaking Finns. The present study is a companion study to previous research conducted using the same methods and corpus that focused on the noun phrase complexity of 9th grade pupils and university students of English. The present study answers the questions what kinds of noun phrases upper secondary school students produce in their texts and how the texts of Finnish L1 upper secondary school students and pupils studying under the International Baccalaureate programme differ from each other. The data consists of 15 written texts by the upper secondary school subjects and 13 texts from the pre-IB group. The texts are analysed by counting the number of simple and complex noun phrases found in them, and the noun phrases are analysed based on the premodification and postmodification of noun phrases found. The averages are compared between the two groups as well as between the results of the previous study on both younger and older learners of English to assess and analyse the differences in the complexity of noun phrases produced by the three groups. The results of the study indicate that the high-achieving group formed of pre-IB students had longer and more complex noun phrases than the upper secondary school language learners as well as producing more noun phrases overall. When comparing the results to previous studies, the pre-IB group showed a tendency to produce more complex noun phrases than Finnish language learners in general and the upper secondary school data was in line with previous studies on the same corpus. The upper secondary school group showed also a clear improvement from the noun phrase complexity of 9th grade Finnish English learners, with the relationship between the production of simple and complex noun phrases being nearly equal with 50.45% simple noun phrases and 49.54% complex noun phrases. The complex noun phrases produced by the upper secondary school students consisted mostly of adjective premodification with adjectives, nouns and adverbs and of postmodification with prepositional phrases.
Keywords: SLA, L2, noun phrase complexity, second language acquisition, learner language